The IVP Bible background commentary : Old Testament - Walton, John H., 1952-; Matthews, Victor Harold; Chavalas, Mark W. (Mark William), 1954- (Downers Grove, Ill. : InterVarsity Press, 2000)
"The narratives, genealogies, laws, poetry, proverbs and prophecies of the Old Testament are deeply rooted in history. Archaeologists, historians and social scientists have greatly advanced our knowledge of the ancient world of the Bible. When we illuminate the stories of Abraham or David, the imagery of the Psalms or Proverbs, or the prophecies of Isaiah or Jeremiah with this backlight of culture and history, these texts spring to new life." "This commentary joins The IVP Bible Background Commentary: New Testament in giving historical, social and cultural background for each Old Testament passage. From Genesis through Malachi it gathers and condenses an abundance of specialized knowledge and makes it available to ordinary readers of the Old Testament. It will enrich your study of these biblical books in a way that no other commentary can do."--Jacket.
Pentateuch -- Historical literature -- Wisdom and poetic literature -- Prophetic literature.
Includes bibliographical references (pages 10-20) and index.
Keywords: Bible. -- Commentaries; Bible. O.T. - Commentaries; Commentaries